Fußwallwunder Leicester City - Auch in der Bundesliga möglich? Ein ökonomischer Vergleich des Wettbewerbs in der Bundesliga mit der englischen Premier League - Aykanat, Cengiz

Economics of Corruption and Crime: An Interdisciplinary Approach to Behavioral Ethics - Dimant, Eugen

On the Design and Defense of Networks - An Experimental Investigation - Endres, Angelika Elfriede

On the abuse of market power - an economic perspective of Microsoft antitrust cases - Pehlivan, Muhammet

Strategic Network Disruption and Defense - Hoyer, Britta; De Jaegher, Kris (Journal of Public Economic Theory)
We study a game between a network designer, who uses costly links to connect nodes in a network, and a network disruptor who tries to disrupt the resulting network as much as possible by deleting either nodes or links. For low linking costs networks with all nodes in symmetric positions are a best response of the designer under both link deletion and node deletion. For high linking costs the designer builds a star network under link deletion, but for node deletion excludes some nodes from the network to build a smaller but stronger network. For intermediate linking costs the designer again builds a symmetric network under node deletion but a star‐like network with weak spots under link deletion.

By-product mutualism and the ambiguous effects of harsher environments – A game-theoretic model - De Jaegher, Kris; Hoyer, Britta (Journal of Theoretical Biology)
We construct two-player two-strategy game-theoretic models of by-product mutualism, where our focus lies on the way in which the probability of cooperation among players is affected by the degree of adversity facing the players. In our first model, cooperation consists of the production of a public good, and adversity is linked to the degree of complementarity of the players׳ efforts in producing the public good. In our second model, cooperation consists of the defense of a public, and/or a private good with by-product benefits, and adversity is measured by the number of random attacks (e.g., by a predator) facing the players. In both of these models, our analysis confirms the existence of the so-called boomerang effect, which states that in a harsh environment, the individual player has few incentives to unilaterally defect in a situation of joint cooperation. Focusing on such an effect in isolation leads to the "common-enemy" hypothesis that a larger degree of adversity increases the probability of cooperation. Yet, we also find that a sucker effect may simultaneously exist, which says that in a harsh environment, the individual player has few incentives to unilaterally cooperate in a situation of joint defection. Looked at in isolation, the sucker effect leads to the competing hypothesis that a larger degree of adversity decreases the probability of cooperation. Our analysis predicts circumstances in which the "common enemy" hypothesis prevails, and circumstances in which the competing hypothesis prevails.

Marktmissbrauch in der Internetökonomie - Eine wettbewerbspolitische Analyse - Kesmen, Belma

Do talented women shy away from competition? - Hoyer, Britta; van Huizen, Tomas; Keijzer, Linda; Rezai Khavas, Tahere; Rosenkranz, Stephanie
We study the willingness to compete in a cognitive task among an entire cohort of fresh man business and economics students. Combining data from a lab-in-thefield experiment with university admissions data, we trace the gender gap in competitiveness at different levels of high school performance. Our results confirm that, on average, men choose to compete more often. The gender gap disappears, however, among students with above average high school performance. Female high school top performers are equally competitive as their male counterparts. In fact, the overall gender gap is entirely driven by the group of female high school underperformers who shied away from competition, even when they performed well in our task. Overall, our findings suggest that high school grades are more than just a signal of cognitive abilities, because they seem to influence the receivers selfperception of his or her performance in a competitive environment involved in later on in life.

Wettbewerb im Internet - Eine wettbewerbspolitische Analyse des E-Commerce - Kaczorkowski, Jessica

Selektive Vertriebssysteme am Fallbeispiel der Adidas AG - eine wettbewerbspolitische Beurteilung - Zindler, Finn

Koordinierter Patentschutz in einer globalisierten Welt - Effizienz- und Anreizwirkungen auf die Arzneimittelversorgung in Entwicklungsländern - Kirsch, Michelle

Fusionen von gesetzlichen Krankenversicherungen zu den Effizienz- und Wechselwirkungen - Osburg, Christina

Fair Trade - Eine neue Perspektive in der internationalen Handelspolitik - Materna, GinaJoanna

Fair Trade - An economic investigation of benefits and drawbacks - Goronczewski, Patricia

Entwicklung von Ablösesummen und Gehälter in der Fußball-Bundesliga - Salary Caps als mögliches Modell der Chancengleichheit - Plonka, Dennis

Diffusion of Innovations in Social Networks - Kunisch, Christina

Die Einführung der EU-Merger Guidelines - Effizienz und Wohlfahrtswirkungen - Topal, Barlas

Verkaufsbeschränkungen auf Onlinemarktplätzen - Eine wettbewerbspolitische Analyse am Fallbeispiel der Adidas AG - Menne, Maria Reinhild

Zur Verbreitung von Informationen in sozialen Netzwerken - eine wirtschaftspolitische Analyse - Schulz, Hannah

Zur Ausbreitung und Behinderung von Epidemien - Eine Netzwerkanalyse - Drigalsky, Liesa